A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae) - Jorge, Nina Castro; Cavalleri, Adriano; Bedetti, Cibele Souza; Isaias, Rosy Mary Dos Santos (Zootaxa, 2016)
Holopothrips striatus sp. n. is described inducing leaf-galls on Myrcia retorta (Myrtaceae) in Southern Brazil. The thrips is one of the few species of Holopothrips known to have the metanotum with striate rather than reticulate sculpture. The galls are green with brownish spots, and are characterised by a mix of folding and rolling of the leaf lamina upwards.